2021
DOI: 10.3390/ijerph18030881
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian Tube Function Assessment after Radiofrequency Turbinate Reduction in Atopic and Non-Atopic Patients

Abstract: (1) Background: Inferior turbinates’ hypertrophy is often associated with Eustachian tube dysfunction (ETD); radiofrequency turbinate reduction (RTR) may provide a long-term improvement of nasal obstruction and ETD-related symptoms. (2) Aim: The study aimed to compare ETD in atopic and non-atopic patients before and after RTR and to investigate the correlation between tympanometry and Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7). (3) Methods: Ninety-seven patients, ranging from 33 to 68 years old, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[14,15] Enteral nutrition through a nasoenteral tube holds significant clinical importance for critically ill patients, as it can effectively reduce the likelihood of aspiration pneumonia resulting from gastrointestinal reflux. [16] Conventional methods for nasointestinal tube placement include endoscopic-assisted tube placement, X-ray fluoroscopyassisted tube placement, and blind insertion. [12,17,18] Endoscopicassisted catheterization currently boasts one of the highest success rates, but its invasiveness, complex procedure, timeconsuming nature, high cost, and associated risks limit its usage and promotion for nasointestinal tube implantation.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] Enteral nutrition through a nasoenteral tube holds significant clinical importance for critically ill patients, as it can effectively reduce the likelihood of aspiration pneumonia resulting from gastrointestinal reflux. [16] Conventional methods for nasointestinal tube placement include endoscopic-assisted tube placement, X-ray fluoroscopyassisted tube placement, and blind insertion. [12,17,18] Endoscopicassisted catheterization currently boasts one of the highest success rates, but its invasiveness, complex procedure, timeconsuming nature, high cost, and associated risks limit its usage and promotion for nasointestinal tube implantation.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 and TMPRSS2 are also present in the eustachian tube, middle ear and cochlea, suggesting that these tissues are susceptible to SARS-CoV-2 infection [ 18 ]. Furthermore, the congestion of the turbinates and eustachian tube can promote the transition of viruses and bacteria in the middle ear [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Martines et al compared ETD symptoms in atopic and non‐atopic patients before and after radiofrequency turbinate reduction 4 . Initially, 113 participants were enrolled in an observational cohort study of patients with a confirmed diagnosis of bilateral ITH, at least one ETD symptom and no response to medical management after 3 months.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Martines et al compared ETD symptoms in atopic and non-atopic patients before and after radiofrequency turbinate reduction. 4 Initially, 113 participants were enrolled in an observational cohort study of patients with a confirmed diagnosis of bilateral ITH, at least one ETD symptom and no response to medical management after 3 months. Study metrics included ETDQ-7 scores, William's test (audiometer measuring ear pressure under three conditions: during rest, swallow, and Valsalva), tympanometry, and allergy skin tests.…”
Section: Literature Reviewmentioning
confidence: 99%